Pengaruh Program Keluarga Harapan (PKH) terhadap Tingkat Pendapatan Nelayan di Desa Suka Maju Kecamatan Simeulue Timur Kabupaten Simeulue - Asia, Siti Nur; Wahyuningsih, Yayuk Eko (Medan Resource Center, 2023)
The various welfare enhancement programs initiated by the Indonesian government to alleviate poverty include the Conditional Cash Transfer Program, known as the Program Keluarga Harapan (PKH), which provides conditional social assistance to families identified as beneficiaries of the program. This research aims to analyze the Impact of the Keluarga Harapan Program on the Income of Fishermen in the village of Suka Maju, East Simeulue District, Simeulue Regency. The method employed is a quantitative approach, utilizing primary data collected from 17 fishing households who are recipients of PKH in the village of Suka Maju, East Simeulue, through saturation sampling techniques.The research findings indicate a significant influence of the PKH program on the income of fishermen in the village. Furthermore, the effectiveness aspect reveals that participants receiving PKH assistance in Suka Maju village are categorized as effective and appropriately targeted. There is an increase in fishermen's income before and after receiving PKH assistance, amounting to Rp15,635,294.12, representing a 19.19% rise from their income prior to PKH assistance. The results of the t-test and significance value (sig.) are 0.001, leading to the conclusion that P(0.01)<?(0.05), suggesting a significant difference in the income of fishing households before and after receiving PKH assistance.